Behavior of HPC with Fly Ash after Elevated Temperature - Huai-Shuai Shang; Ting-Hua Yi (Advances in Materials Science and Engineering)
For use in fire resistance calculations, the relevant thermal properties of high-performance concrete (HPC) with fly ash were determined through an experimental study. These properties included compressive strength, cubic compressive strength, cleavage strength, flexural strength, and the ultrasonic velocity at various temperatures (20, 100, 200, 300, 400 and 500∘C) for high-performance concrete. The effect of temperature on compressive strength, cubic compressive strength, cleavage strength, flexural strength, and the ultrasonic velocity of the high-performance concrete with fly ash was discussed according to the experimental results. The change of surface characteristics with the temperature was observed. It can serve as a reference for the maintenance, design, and the life prediction of high-performance concrete engineering, such as high-rise building, subjected to elevated temperatures.